PENGARUH PERUBAHAN RATING OBLIGASI TERHADAP MARKET MODEL - ., Amirah (PERMANA, 2011)
The purpose of this research is to examine the effect of obligation rating change both in upgrade and downgrade on the sensitivity of relationship between stock return and return market, an then to examine the effect of obligation rating change to the intercept and coefficient in the model. The choosing of the samples done by purposive sampling with the requirement all the companies publishing their stock and obligation in Indonesian Stock Exchange in 2000-2007. the examination done by time series both daily, weekly, and monthly in 31 companies by 64 observation, they are 51 upgrade, and 13 downgrade. Statistic’s method done to examine the first hypothesis is simple linier regression with dummy variable. While, the second hypothesis was examined by using chow test. The result of this research shows that upgrade obligation rating change decreases the sensitivity of relationship between stock return and market return. On the opposite, the downgrade obligation rating change increases the sensitivity of relationship between stock return and return market. The effect of obligation rating change which is not significant was indicated because the obligation rating change has been anticipated by the investors so that this case causes no change to the intercept and coefficient in the model. Key word: obligation rating change, Single Index Model